Proses Fabrikasi dan Kontrol Kualitas Hatch Door Serta Efisiensi Mesin PT. Mitsubishi Jaya Elevator dan Escalator - Marshel Daniel; Viktor Naubnome; Aa Santosa (Jurnal Ilmiah Wahana Pendidikan, 2022)
Elevator or elevator is a vertical means of transportation in a multi-storey building, which serves to facilitate human activities in carrying out their routines. This research is a quantitative research with direct observation to the field of documentation, as well as. The result of this research is the hatch door production process at PT. Mitsubishi Jaya Elevator And Escalator which has a production process flow including the preparation process, shearing, turret punching, v - cut, bending, welding, painting, oven processes, quality control, and packing, while the results of the calculation of machine efficiency time at daily output are 33, 3% while the overall is 55.6%.